The prognostic impact of preoperative body composition in perihilar and intrahepatic cholangiocarcinoma. Issue 9 (26th May 2022) - Lurje, Isabella; Czigany, Zoltan; Eischet, Sarah; Bednarsch, Jan; Ulmer, Tom Florian; Isfort, Peter; Strnad, Pavel; Trautwein, Christian; Tacke, Frank; Neumann, Ulf Peter; Lurje, Georg
Abstract: Cholangiocarcinoma (CCA) is a rare but highly aggressive malignancy of the biliary system. Although it is amenable to surgical resection in early disease, outcomes are frequently dismal. Here, we investigated the prevalence of body composition (BC) alterations and their prognostic role for surgical patients with intrahepatic (iCCA) and perihilar (pCCA) disease. Patients undergoing curative‐intent surgery for iCCA or pCCA between 2010 and 2019 at University Hospital Aachen were included. Axial computed tomography images were retrospectively assessed with a segmentation tool (3D Slicer) at the level of the third lumbar vertebra to determine lumbar skeletal muscle (SM) index, mean SM radiation attenuation, and visceral fat area. The related BC pathologies sarcopenia, myosteatosis, visceral obesity, and sarcopenic obesity were determined using previously described cutoffs. A total of 189 patients (86 with iCCA, 103 with pCCA) were included. Alterations of BC were highly prevalent in iCCA and pCCA, respectively: sarcopenia, 33% (28/86) and 39% (40/103); myosteatosis, 66% (57/86) and 66% (68/103); visceral obesity, 56% (48/86) and 67% (69/103); sarcopenic obesity, 11% (9/86) and 17% (17/103). Sarcopenia and myosteatosis did not have a significant prognostic role for disease‐free survival (DFS) and overall survival (OS). Patients with iCCA with sarcopenic obesity (n = 9) had significantly shorter OS than patients without sarcopenic obesity (n = 7; log‐rank p  = 0.002; median OS, 11 months and 31 months; 1‐year mortality, 55.6% [5/9] and 22% [17/77]; 5‐year mortality, 88.9% [8/9] and 61% [47/77], respectively). In multivariable analysis, only tumor‐related risk factors remained prognostic for DFS and OS. Sarcopenic obesity may affect clinical outcomes after curative‐intent surgery for iCCA, indicating that imaging‐based analysis of BC may hold prognostic value for long‐term survival and could aid preoperative patient selection. Abstract : Body composition ‐ the amount, distribution and quality of fat and muscle ‐ can be assessed on routine computed tomography scans. Alterations of Body Composition are highly frequent in patients undergoing surgery for cholangiocarcinoma. Patients with intrahepatic cholangiocarcinoma may be at a higher risk for dismal outcomes if they have a high Body Mass Index while exhibiting very low muscle mass (sarcopenic obesity).image